The influence of powder characteristics on densification behavior and microstructure evolution of W-Cr-Zr alloy consolidated by field-assisted sintering technology. (November 2022) - Wang, W.J.; Tan, X.Y.; Yang, S.P.; Mao, Y.R.; Luo, L.M.; Zhu, X.Y.; Litnovsky, A.; Coenen, J.W.; Linsmeier, Ch.; Wu, Y.C.
Abstract: In the present study, the influence of powder characteristics on the densification behavior and microstructure evolution of the W-Cr-Zr alloy during consolidation was investigated. The W-Cr-Zr alloy powders were prepared through mechanical alloying in different modes, i.e. continuous mechanical alloying (CMA) and intermittently mechanical alloying (IMA). It can be found that the IMA powders have a higher grain boundary density and homogenous microstructure, which exhibits a better sintering performance than the CMA powders. The IMA powders are capable of full densification and homogenization after sintering at low temperature (1395 °C), with the grain size approaching 284 nm. Through the characterization of antioxidant properties, it was confirmed that the alloy prepared using IMA powders has an excellent anti-oxidation performance. Graphical abstract: Image 1 Highlights: The powders characteristic was considered to manufacture W-Cr-Zr alloy. The homogeneous and fine-crystal alloy powder has high sintering performance. W-Cr-Zr alloy has high relative density, homogeneous and fine-grained microstructure.